Management of acute COPD exacerbations in the internal medicine departments in Israel–a national survey - Bar-Shai, Amir; Freund, Ophir; Ovdat, Tal; Segel, Michael J.; Klempfner, Robert; Elis, Avishay (Frontiers in Medicine, 2023)
Background Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Acute exacerbations of COPD (AECOPD) drastically affect the clinical course of the disease. We aimed to evaluate the treatment of AECOPD in the internal medicine departments in Israel, nationwide. Methods The COPD Israeli survey (COPDIS) is the first national survey of patients admitted with AECOPD to internal medicine departments between 2017 and 2019. The survey includes prospective (n = 344) and retrospective (n = 1,166) data from 13 medical centers. We analyzed the pre-hospital, in-hospital, and pre-discharge care. Hospital evaluation, outcomes and discharge recommendations were assessed as well. Results The mean (±SD) age was 74 (±8) years, and 54% were males. 74% had comorbidities, and 88% had a diagnosis of COPD in their history. 70% of the patients received systemic steroids and antibiotics during their hospitalization, yet upon discharge, a lower rate of antibiotics prescription (10%) was found. Treatment with most long-acting bronchodilators dramatically dropped during admission, compared with their pre-hospital use. Overall, a long-acting bronchodilator (LABD) was used by 47% before admission, 28% in-hospital, and was prescribed to 54% at discharge. The discharge plan included a referral to pulmonary rehabilitation in only 11% and a smoking cessation recommendation in 43% of active smokers. The in-hospital mortality was 3% and the 1-year mortality rate was 25%. In multivariate analysis, performing a chest X-ray (adjusted OR 0.64, 95% CI 0.46–0.90) and prescribing LABD at discharge (AOR 0.73, 95% CI 0.57–0.95) were independent predictors for lower 1-year mortality. Conclusion Our results demonstrate AECOPD characteristics in Israel, and highlight several important gaps in AECOPD healthcare, which must be addressed to improve patient care.